Groundwater Characteristic and Fresh Water Supplying System of the East Slope Merapi Volcano - Priyana, Yuli; Sigit, Agus Anggoro (Forum Geografi, 2002)
slope of Merapi Volcano in Boyolali. The aims of this study are first to know the characteristic of groundwater in every morphological unit, second to know supplying system of fresh water in every each unit.The method used is survey method. The sampling use to know the characteristic groundwater both quality and quantity of the water, and supplying system of fresh by using area sampling. As basic of stratification of its region is morphological unit. Analysis method used is tabulation, laboratory analysis, and graphic analysis to describe its space.The result of the study shows that the quality of groundwater in every morphological unit is good enough, but in general the contents of element Ca, Mg, N03, CI, SO4, HCO3 shows that the lower the region is, the higher the content of the element . But if it is seen from the depth of its groundwater, so that the ï¬uvial volcanic plain is the shallowest, then the ï¬uvial volcanic foot plain and the last the volcanic foot area. Supplying system of fresh water, which derived from the dominant of well water, is especially used in morphological unit in ï¬uvial